The role of perceptions of transformational leadership style on organizational citizenship behavior in employees - Prayuda, Rafie Zaidan (Journal of Industrial Engineering & Management Research, 2023)
This research aims to determine the relationship between transformational leadership style and organizational citizenship behavior in employees. This research is correlational research with a quantitative approach. The population of this research is employees. Participants in this research used the entire population, namely 435 employees. The research instrument uses a transformational leadership scale and an organizational citizenship behavior scale which is prepared using a Likert scale. Data analysis was carried out using the Product Moment correlation technique. The research results show that there is a significant positive relationship between transformational leadership and organizational citizenship behavior, or it can be concluded that the higher the transformational leadership, the higher the organizational citizenship behavior and conversely the lower the transformational leadership, the lower the organizational citizenship behavior.